1987
DOI: 10.1002/bjs.1800740527
|View full text |Cite
|
Sign up to set email alerts
|

Response of multicentric desmoid tumours to tamoxifen

Abstract: pattern in aetiology of pancreatitis in an urban Swedish area. B r J Surg 1979; 66: 159-61. Imrie CW, McKay AJ, Benjamin IS, Blumgart LH. Secondary acute pancreatitis: aetiology, prevention, diagnosis and management. Br J Surg 1978; 65: 399402. Morrisey R, Berk JE, Fridhandler L, Pelot D. The nature and significance of hyperamylasemia following operation. Ann Surg 1974; 180: 67-71. Imrie CW. Observations on acute pancreatitis. Br J Surg 1974; 61: 53944. Case report 16. Jacobs ML, Daggett WM, Civetta JM et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 9 publications
0
18
0
3
Order By: Relevance
“…10 Antagonistic effects on both platelet-derived growth factor-␤ (PDGF-␤) production and prostaglandin metabolism also may contribute to the efficacy of this drug. 31,[33][34][35][36][37] Conventional cytotoxic therapy also has demonstrated anecdotal success, occasionally producing prolonged progression-free periods. 11,26,35,38 -44 In our experience, prolonged treatment confers a proportionally longer progression-free period; however, toxicity limits the duration and success of this approach.…”
Section: Results Both Patients Demonstrated Ongoing Radiographic Andmentioning
confidence: 99%
“…10 Antagonistic effects on both platelet-derived growth factor-␤ (PDGF-␤) production and prostaglandin metabolism also may contribute to the efficacy of this drug. 31,[33][34][35][36][37] Conventional cytotoxic therapy also has demonstrated anecdotal success, occasionally producing prolonged progression-free periods. 11,26,35,38 -44 In our experience, prolonged treatment confers a proportionally longer progression-free period; however, toxicity limits the duration and success of this approach.…”
Section: Results Both Patients Demonstrated Ongoing Radiographic Andmentioning
confidence: 99%
“…Finally, some authors have also reported objective responses following endocrine manipulations with antiestrogen [23,25,30,36,38,41,43,55,63], antiprostaglandin [55], and nonsteroidal anti-inflammatory drugs [24,26,45,49,55]. Other authors, however, reported treatment failures [5,22,26,39,63].…”
Section: Discussionmentioning
confidence: 89%
“…Desmoi de wur den ex pe ri men tell durch Östro-gen appli ka tio nen in du ziert [28,48]. Anti östro ge ne wie Ta mo xi fen üben einen wachs tums hem men den Ef fekt aus [8,16,28,30,43,48]. Östro gen re zep to ren wur den in 36, An ti östro gen re zep to ren in 79 aller Des moi de ge fun den [20,29,42,45].…”
Section: äTio Lo Gieunclassified